2015
DOI: 10.1007/s11064-015-1651-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Cytosolic ATP Levels in Cultured Glutamatergic Neurons During NMDA-Induced Synaptic Activity Supported by Glucose or Lactate

Abstract: We have previously shown that synaptic transmission fails in cultured neurons in the presence of lactate as the sole substrate. Thus, to test the hypothesis that the failure of synaptic transmission is a consequence of insufficient energy supply, ATP levels were monitored employing the ATP biosensor Ateam1.03YEMK. While inducing synaptic activity by subjecting cultured neurons to two 30 s pulses of NMDA (30 µM) with a 4 min interval, changes in relative ATP levels were measured in the presence of lactate (1 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…We found that axonal ATP levels were significantly lower during HFS when nerves were incubated with lactate or pyruvate as the sole energy substrate. This suggests that lactate/pyruvate alone does not support ATP production as well as glucose and confirms observations in cultured cerebellar granule cells with repetitive activation of NMDA-receptors (Lange et al, 2015). …”
Section: Discussionsupporting
confidence: 84%
“…We found that axonal ATP levels were significantly lower during HFS when nerves were incubated with lactate or pyruvate as the sole energy substrate. This suggests that lactate/pyruvate alone does not support ATP production as well as glucose and confirms observations in cultured cerebellar granule cells with repetitive activation of NMDA-receptors (Lange et al, 2015). …”
Section: Discussionsupporting
confidence: 84%
“…More recently, genetically encoded optical sensors for ATP have been introduced that enable the direct study of intracellular ATP levels with high temporal and spatial resolution by fluorescence imaging. These sensors change either their fluorescence or luminescence properties depending on ATP concentration (Imamura et al, 2009;Berg et al, 2009;Nakano et al, 2011;Tantama et al, 2013;Rangaraju et al, 2014) and so far have been mainly used to study neuronal ATP homeostasis and regulation (Connolly et al, 2014;Rangaraju et al, 2014;Toloe et al, 2014;Lange et al, 2015;Pathak et al, 2015). Here, we took advantage of ATeam1.03 YEMK , a fluorescent, FRET-based sensor for ATP (Imamura et al, 2009), to study ATP dynamics in astrocytes during exposure to the neurotransmitters glutamate and dopamine, as well as the effect of different energy substrates (glucose, lactate) on ATP changes in those cells.…”
Section: Introductionmentioning
confidence: 99%
“…ATP sources change dynamically with neuronal activity and several mechanisms account for this fine-tuning response. First, neuronal mitochondria are capable of raising ATP synthesis in response to increased synaptic stimuli (Jekabsons and Nicholls 2004;Connolly et al 2014;Toloe et al 2014;Lange et al 2015;Rangaraju, Calloway, and Ryan 2014). Although the molecular meditators for this activation are not completely elucidated, the increase of the respiratory rate of an isolated mitochondria correlates well with the ADP concentration (G. C. Brown 1992), and neuronal mitochondrial function has been satisfactorily modeled considering the changes in ATP and ADP levels (Berndt, Kann, and Holzhütter 2015).…”
Section: Brown and Ransom 2007)mentioning
confidence: 99%
“…Several evidences demonstrate that it is reasonable to assume a constant value for energy availability for neurons over the long term (energetic homeostasis). For instance, cultured neurons exhibit a steady value for free adenosine triphosphate (ATP) in basal conditions, which transiently decrease during the induction of glutamatergic synaptic activity through various energy challenges (Marcaida et al 1997;Marcaida et al 1995;Lange et al 2015;Rangaraju, Calloway, and Ryan 2014). This tight energy management suggests a relevant role for neuronal energy homeostasis on neuronal and network functional properties.…”
Section: Introductionmentioning
confidence: 99%